Features of Pathogenesis of Human Viral Infections and Antiviral Drugs - Aquaro, Stefano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Among infectious diseases, viral infections are the leading cause of death worldwide, especially in the most low-income countries, particularly in young children. Most of the human viruses are all well characterized in terms of structure, life-cycle, tropism, and associated primary pathologies, but many of the pathogenetic mechanisms underlying their ability to cause acute infection, persist or reactivate in the host and cause chronic and/or degenerative damage, and still need to be fully clarified. At the same time, it seems necessary to develop novel therapeutic approaches and rationale, and possibly more potent antiviral compounds that are addressed to novel targets.